Economic Growth and Poverty: The Mediating Effect of Employment - Purnomo, Sodik Dwi; Istiqomah, Istiqomah (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
The results of previous research on the relationship between economic growth and poverty have shown inconclusive results. This could be due to the fact that the relationship between these variables is indirect. Therefore, this study tries to introduce employment opportunity as a mediating variable. In addition, the authors also examined the effect of control variables consisting of dependency ratio, education, and infrastructure. The data used in this study are panel data of 6 provinces on Java Island in the period of 2000-2017. The methods used in this study are path analysis and multiple linear regression. The resultsÃ‚Â  show that employment opportunity perfectly mediates the relationship between poverty and economic growth. This study also found that dependency ratio and education had a significant effect on poverty, while infrastructure had a negative, but insignificant effect on poverty. The perfect mediating effect implies that economic growth will reduce poverty only if the economic growth is able to generate employment opportunities. These findings imply the importance of inclusive growth that gives access to the poor to work and business opportunities.